A case of post-operative stenosis caused by colonic ischemia after low anterior resection for rectal cancer, followed by delayed colo-anal anastomosis. Issue 5 (18th May 2022) - Uchiyama, Shuichiro; Ikeda, Naotaka; Oyama, Tomohiro; Eguchi, Mayumi; Ito, Ayaka; Sato, Rikiya; Toyosaki, Ryoichi; Kitazono, Masaki; Suenaga, Toyokuni
Abstract: Cases of delayed colo-anal anastomosis (DCAA) are currently reported instead of the colo-anal anastomosis with a protective loop ileostomy for rectal cancer. Post-operative colonic ischemia is considered as one of the serious complications of colorectal resection. Although indication of DCAA should be carefully selected, we experienced a case of post-operative stenosis caused by colonic ischemia after low anterior resection for rectal cancer, followed by this procedure.